An archaeology of West Polynesian prehistory - Smith, Anita (Anita Jane), 1957-; Australian National University. Research School of Pacific and Asian Studies (Canberra : Pandanus Books, Research School of Pacific and Asian Studies, Australian National University, 2002)
There can be little doubt on linguistic evidence that East Polynesia was first settled from West Polynesia. The author argues, however, that the related archaeological record has been made to fit with this dominant interpretative paradigm. Her objective assessment of the material evidence contradicts the popularly held view.
Includes bibliographical references
Keywords: Prehistoric peoples -- Oceania; Excavations (Archaeology) -- Oceania; Antiquities, Prehistoric -- Oceania; Oceania -- Colonization